2016
DOI: 10.1001/jamacardio.2016.1687
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Palliative Care Use in Veterans With Severe Heart Failure Using a Large National Cohort

Abstract: Methods | Using the 20% random sample of fee-for-service Medicare beneficiaries aged 65 years or older in the carrier and enrollment data from 2008 through 2012, we assessed 99m Tc radiotracer use in the approximately 2 million cardiac stress tests with SPECT-MPI performed during these years, using codes A9500 and A9502 to identify 99m Tc-labeled radiotracers. We calculated population-based rates of SPECT-MPI as well as rates for alternative testing modalities (stress echocardiography, computed tomography coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…Forty of the 43 identified studies were non-intervention studies, using the following methods: national registry/chart review (Arestedt et al, 2018;Bakitas et al, 2017;Connor, Pyenson, Fitch, Spence, & Iwasaki, 2007;Formiga, Espel, Chivite, & Pujol, 2002;Johnson, Parsons, Raw, Williams, & Daley, 2009;Thorns, Gibbs, & Gibbs, 2001;Unroe et al, 2011;Zambroski et al, 2005), interviews (Gerlich et al, 2012;Glogowska et al, 2016;Gott et al, 2008;Hupcey, Penrod, & Fenstermacher, 2009;Kavalieratos, Mitchell et al, 2014;Kimani, Murray, & Grant, 2018;Murray et al, 2007;Selman, Beattie, Murtagh, & Higginson, 2009), retrospective surveys/questionnaire studies (Davidson, Abernethy, Newton, Clark, & Currow, 2013;Kuragaichi et al, 2018;Malik, Gysels, & Higginson, 2013;Mizuno et al, 2016;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), data analysis studies (Chattoo & Atkin, 2009;Greener, Quill, Amir, Szydlowski, & Gramling, 2014;Janssens & Reith, 2013;Mandawat, Heidenreich, Mandawat, & Bhatt, 2016), descriptive study (Abarshi et al, 2010;Cheung et al, 2013;Davidson et al, 2004;Formiga et al, 2008;Greener et al, 2014;Lagman, Walsh, Kunkle, LeGrand, & Davis, 2006;MartÃ-n-Lesende et al, 2016), a retrospective case-control study (Haydar, Lowe, Kahveci, Weatherford, & Finucane, 2004), observational studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty of the 43 identified studies were non-intervention studies, using the following methods: national registry/chart review (Arestedt et al, 2018;Bakitas et al, 2017;Connor, Pyenson, Fitch, Spence, & Iwasaki, 2007;Formiga, Espel, Chivite, & Pujol, 2002;Johnson, Parsons, Raw, Williams, & Daley, 2009;Thorns, Gibbs, & Gibbs, 2001;Unroe et al, 2011;Zambroski et al, 2005), interviews (Gerlich et al, 2012;Glogowska et al, 2016;Gott et al, 2008;Hupcey, Penrod, & Fenstermacher, 2009;Kavalieratos, Mitchell et al, 2014;Kimani, Murray, & Grant, 2018;Murray et al, 2007;Selman, Beattie, Murtagh, & Higginson, 2009), retrospective surveys/questionnaire studies (Davidson, Abernethy, Newton, Clark, & Currow, 2013;Kuragaichi et al, 2018;Malik, Gysels, & Higginson, 2013;Mizuno et al, 2016;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), data analysis studies (Chattoo & Atkin, 2009;Greener, Quill, Amir, Szydlowski, & Gramling, 2014;Janssens & Reith, 2013;Mandawat, Heidenreich, Mandawat, & Bhatt, 2016), descriptive study (Abarshi et al, 2010;Cheung et al, 2013;Davidson et al, 2004;Formiga et al, 2008;Greener et al, 2014;Lagman, Walsh, Kunkle, LeGrand, & Davis, 2006;MartÃ-n-Lesende et al, 2016), a retrospective case-control study (Haydar, Lowe, Kahveci, Weatherford, & Finucane, 2004), observational studies …”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in 12 different countries: USA, Canada, UK, Sweden, Germany, Spain, Netherlands, Kenya, Australia, China, South Korea, and Japan. Care settings included accessing palliative care in the following three settings: hospital (Bakitas et al, 2013;Glogowska et al, 2016;Greener et al, 2014;Hupcey, Kitko, & Alonso, 2016;Johnson et al, 2009;Kavalieratos, Mitchell et al, 2014;Kim & Hwang, 2014;Kimani et al, 2018;Kuragaichi et al, 2018;Lagman et al, 2006;Mandawat et al, 2016;Mizuno et al, 2016;Rogers et al, 2017;Selman et al, 2009;Wiskar et al, 2017), at home (Davidson et al, 2013(Davidson et al, , 2004Enguidanos et al, 2005;Haydar et al, 2004;MartÃ-n-Lesende et al, 2016;Pattenden et al, 2013;Roig et al, 2006;Taitel et al, 2012;Wong et al, 2016), and outpatient settings (Gandesbery, Dobbie, & Gorodeski, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent audit of 54 654 patients admitted to hospital with HF in England and Wales between 2013–14, only 4% were referred to SPC during admission . Two recent studies in the United States retrospectively analysed large HF databases to identify patients thought likely to have SPC needs . These studies identified 4474 and 32 270 patients, respectively, thought to have SPC needs, of whom 7.6% and 9.6% were seen by SPC services.…”
Section: Discussionmentioning
confidence: 99%
“…[280][281][282][283] Among patients hospitalized with an ACS, palliative care use declined from 6% in 1997 to 2% in 2013. 284 The reasons underpinning these low referral rates remain unclear, but provider misperceptions about palliative services are a likely contributor.…”
Section: Palliative Care Use and Perceptions In Cardiovascular Practicementioning
confidence: 99%